The Cultural Significance of Transitioning from Traditional Hindu Creation Ceremonies Using Firewood to Modern Practices Employing Gas as Fuel - Dewa Putu Wipayana Kusuma; Budhi Waskito; Noning Verawati (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
This research investigates the cultural significance of the transformation in the Ngaben ceremony, a central cremation ritual in Balinese Hindu tradition, focusing on the shift from traditional firewood-based methods to modern gas-based cremation practices. The Ngaben ceremony holds profound religious, philosophical, and social meaning, symbolizing the liberation of the soul from worldly ties and its journey to the afterlife. In recent decades, technological advancements and socio-environmental considerations have prompted many communities in Bali to adopt gas cremation systems, offering greater efficiency, reduced environmental impact, and lower operational costs. Using a qualitative ethnographic approach, this study draws on in-depth interviews, participant observation, and document analysis to explore how this transition affects cultural meaning, community values, and religious interpretations. The research compares the symbolic elements embedded in traditional and modern methods, examining how changes in materials, process duration, and ceremonial aesthetics influence the perceived authenticity and spiritual significance of the ritual. Findings reveal that while some community members view the adoption of gas cremation as a pragmatic adaptation that aligns with contemporary needs, others express concern about the erosion of cultural heritage and the diminished role of traditional craftsmanship. Furthermore, the study highlights the adaptive strategies employed by Balinese Hindu communities to integrate modern technology while preserving essential spiritual values, such as maintaining ritual sequences, symbolic offerings, and priest-led prayers. The analysis underscores that cultural transformation within religious practices is not a simple replacement of old methods with new ones, but rather a process of negotiation between tradition and innovation. Ultimately, this research contributes to broader discussions on cultural resilience, religious continuity, and the dynamic interaction between technological change and sacred tradition in contemporary Balinese Hindu society.